The Startup Players Handbook A Roadmap to Building SaaS and Software Companies - Edge, Charles; Pearson, Chip.; Pearson, Amy Larson (Berkeley, CA : Apress : Imprint: Apress, 2023)
Modern startups are on an assembly line from seed to later-stage series financing. As they make that journey, founders need to have a working knowledge of dozens of fields if they're going to scale a company. SaaS is a unique set of skills across those disciplines. This book focuses on gaining a working understanding of what specialists will do in those fields as an organization grows and how founders can leverage the basics to get those capabilities started so once professionals are hired in each, they can hit the ground running with authentic materials. Founders will be pulled in a lot of directions as they find success, so the book looks at what to do with each discipline at each stage of growth. The hardest part to creating a startup is to just start the thing. This book covers when to bootstrap, apply to accelerators, seek seed capital - and where to do those things. It also covers some of the earlier questions like how to write a mission statement, where to find investors, what technical stacks to use, how to HR, how to sell, and more importantly, when a founder should spend time on each discipline. A way to look at the tech stack and the ever-changing landscape to keep technical debt low and the ability to respond to ever-changing market forces high. You will: The nuts and bolts of which type of corporation to found, impacts to taxes, equity, and of course more philosophy. Researching, pricing, and planning to take that wonderful innovation to market and expanding into a portfolio. Leadership styles-each has its place and so we look at ways to level up that domain Management-going beyond inspiration, from those regularly scheduled meetings to helping people grow to task managemen. Basic accounting and finance skills with terms and guidance on revenue treatment.
Chapter 1: The Mission -- Chapter 2: The Philosophy -- Chapter 3: Founding the Company -- Chapter 4: The Product -- Chapter 5: Leadership -- Chapter 6: Management -- Chapter 7: The Humans -- Chapter 8: The Technology -- Chapter 9: Accounting and Finance -- Chapter 10: Sales -- Chapter 11: Marketing -- Chapter 12: Public Relations -- Chapter 13: Support -- Chapter 14: Scale -- Chapter 15: Services -- Chapter 16: Capital -- Chapter 17: Hard Decisions.
Keywords: Entrepreneurship; New business enterprises; Business; Management science; Entrepreneurship; Business and Management